Historiography and Invisible Musics Domestic Chamber Music in Nineteenth-Century Britain - Bashford, Christina (American Musicological Society], [Richmond (Va), 2010)
RESUMEN: A persistent idea in chamber music historiography is that nineteenth-century Britain lacked a significant, serious domestic chamber-music culture of the type so prevalent in Austro-Germany. Such activity is assumed to have dried up ca. 1800, along with indigenous chamber-music composition, to be replaced by music making at the parlor piano and attendance at public concerts. This essay challenges that view and suggests a continuing, coherent subculture of private chamber music spread across Britain, often in unexpected settings and in communities of upper- and middle-class males. Underpinning the analysis is new, suggestive documentation from a range of sources including private diaries, letters, magazines, and auction catalogs. At the same time, many publicly oriented sources are silent about British chamber-music life, or contrast it poorly with Germany. Historical contextualization of this evidence suggests that received thinking in the twentieth century owed much to cultural ideologies embedded in the nineteenth. A knot of British anxieties in the nineteenth century around masculinity, class, intellectualism, and national identity led to the serious, private pursuit of chamber music among men of wealth being downplayed in public, caricatured, or even ignored. While the tenacious positioning of chamber music as inherently German stemmed in part from Germany's construction of its own national identity, it also owed much to the Victorians' tendency to perpetuate a limited view of their own musical culture